New Drug Development An Introduction to Clinical Trials: Second Edition - Turner, J. Rick.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
New Drug Development, 2nd Edition, is a reader-friendly introduction to clinical trials that is written specifically for entry-level professionals in the pharmaceutical, biopharmaceutical, and contract research organization (CRO) industries. It is also excellent reading for seasoned clinical research professionals who wish to refresh their knowledge in areas outside their immediate fields of expertise, and for students of clinical research, pharmacy, medicine, nursing, and allied health professions. While the main focus is on preapproval clinical trials, the book adopts a lifecycle drug development approach, placing these trials in the overall continuum from drug discovery to postmarketing surveillance. It therefore contains brief discussions of medicinal chemistry, nonclinical research, drug manufacturing, and the latest techniques for gathering information concerning adverse drug reactions. This edition builds on the success of the first edition by keeping the discussions that were most helpful to readers, and adding new chapters addressing important contemporary topics in drug development. The chapters dealing with the design and analysis of clinical trials in the first edition received praise from many sources. This new edition incorporates extended discussions of the operational aspects of conducting various kinds of trials, ranging from highly specialized and relatively small cardiac safety studies to very large, multi-site Phase III trials run in several different countries.
New Drug Development -- The Regulatory Environment -- Drug Discovery -- Nonclinical Research -- Designing Clinical Trials -- Conducting Clinical Trials I: Experimental Methodology -- Conducting Clinical Trials II: Operational Execution -- Statistical Analysis -- Statistical Significance -- Clinical Significance -- Sample Size Estimation -- General Safety Assessments -- Efficacy Assessment -- Cardiac and Cardiovascular Safety Assessments -- Manufacturing Small Molecule Drugs and Biologicals -- Postmarketing Surveillance -- Main Themes and Concluding Comments.
Keywords: Medicine; Pharmaceutical technology; Biomedicine; Pharmaceutical Sciences/Technology.